Studi fenomenologi subjective well-being pada pekerja perempuan - Haris Munandar (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2022)
Abstract: This study aims to look at subjective well-being images of female workers at the Amahami City Bima Office and the factors that influence subjective well-being in female workers at the Amahami Market office in Bima City. This research was conducted in the city of Bima for women workers who were married in the age range of 22-45 years who had formal working hours and had worked at least 4 years with a total of 6 research subjects. This study uses qualitative methods with a phenomenological approach. Data analysis techniques are used using interviews. Data analysis method in this study with content analysis method. The sampling technique in this study uses purposive sampling. The results of the study found that the subjective well-being picture of female workers in the Amahami market was fulfilled because the expressions of all subjects related to the subjective well-being component emerged. The perceived life satisfaction such as the needs of living with family is fulfilled, grateful to have a job. The affective component that emerges is to enjoy future oriented activitie / interest, happy with friend / excited, self acceptence, attentive to the hub and work, full of determination to work, worried about the child, and limited time with famil. Researchers also found factors that influence subjective well-being in female workers at Amahami city Bima City are Good Relationship with Co-Workers, Husband Support, Optimism, Family Support, Support from Supperiors, Workload, and Full Day Work. Even though there is a negative affect that is felt by the subject, the subject is still able to accept the situation with the feeling of self-acceptance arising from the subject's expression.Keywords: subjective well-being; worker; womanAbstrak: Penelitian ini bertujuan untuk melihat gambaran subjective well-being pada pekerja perempuan di kantor Pasar Amahami Kota Bima dan faktor-faktor yang mempengaruhi subjective well-being pada pekerja perempuan di kantor Pasar Amahami Kota Bima. Penelitian ini dilakukan di Kota Bima pada pekerja perempuan yang sudah menikah dengan rentang usia 22-45 tahun yang memiliki waktu jam kerja formal serta sudah bekerja minimal 4 tahun dengan jumlah subjek penelitian berjumlah 6 orang. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Tenik analisis data digunakan menggunakan wawancara. Metode analisis data pada penelitian ini dengan metode analisis isi. Teknik sampling pada penelitian ini menggunakan purposive sampling. Hasil penelitian ditemukan bahwa gambaran subjective well-being pekerja perempuan di kantor Pasar Amahami ini tercukupi karena ungkapan dari keseluruhan subjek terkait komponen subjective well-being muncul. Adapun kepuasan hidup yang dirasakan seperti kebutuhan hidup bersama keluarga terpenuhi, bersyukur sudah memiliki pekerjaan. Komponen afektif yang muncul adalah enjoy future oriented activitie/ interest, happy with friend/excited, self acceptence, attentive to the huband’s work, full of determination to work, worried about the child, dan limited time with famil. Peneliti juga menemukan faktor-faktor yang mempengaruhi subjective well-being pada pekerja perempuan di kantor pasar Amahami Kota Bima adalah Good Relationship with Co-Workers, Husband Support, Optimism, Family Support, Support from Supperiors, Workload, dan Full Day Work. Walaupun afek ada afek negatif yang dirasakan subjek, namun subjek tetap mampu menerima keadaanya dengan adanya perasaan penerimaan diri yang muncul dari ungkapan subjek.Kata Kunci: pekerja; perempuan; subjective well-being